CP violation in vacuum neutrino oscillation experiments - Gago, A. M.; Pleitez, V. [UNESP]; Zukanovich Funchal, R. (American Physical Society (APS), 2000)
We discuss the use of the CP asymmetry parameter (ACP) as a possible observable of CP violation in the leptonic sector. In order to do this, we study for a wide range of values of LIE the behavior of this asymmetry for the corresponding maximal value of the CP violation factor allowed by all the present experimental limits on neutrino oscillations in vacuum and the recent Super-Kamiokande atmospheric neutrino result. We work in the three neutrino flavor framework. ©1999 The American Physical Society.